Genetic diversity of 23 STR loci in Guangxi Zhuang population and its phylogenetic relationship with 25 other populations - Li Zhang; Shisheng Zhu; Fan Yang; Xue Bai; Yiren Yao; Jianbo Li (Taylor & Francis Group, 2019)
Aim: To estimate genetic diversity of 23 STR loci included in the DNA TyperTM 25 Kit, and evaluate its effectiveness in forensic application. Subjects and methods: A total of 450 (251 males and 179 females) unrelated healthy individuals from Guangxi Zhuang population were amplified with DNA TyperTM 25 Kit, isolated by the 3730 Series Genetic AnalyzerTM, and genotyped using the GeneMapper ID-X. Genetic parameters and population relationships were analysed. Results: Allele frequencies ranged from 0.001 to 0.5889. The combined power of discrimination (CPD) and the combined power of exclusion (CPE) of the 23 STR loci were 0.999999999999999999 and 0.999996765, respectively. No deviations from Hardy-Weinberg equilibrium and linkage disequilibrium were observed. Inter-population comparison based on Fst, PCA, genetic distance, phylogenetic trees, and MDS showed that Zhuang population clustered with the populations holding a close geographic distance with Zhuang (Guangdong Han and Hainan Li populations). Conclusions: Our study indicated that the 23 autosomal STR loci included in DNA TyperTM 25 Kit can be used as forensic tools for individual identification and parentage testing. Moreover, the result of our mass investigation will enrich the forensic database of Chinese populations and serve for further study of the origin of anthropology.